derive the formula for sigma n power 4
Answers
Answered by
65
Heya
Using Binomial Expansion :
![{x}^{5} - {(x - 1)}^{5} = 5 {x}^{4} - 10 {x}^{3} + 10 {x}^{2} - 5x + 1 {x}^{5} - {(x - 1)}^{5} = 5 {x}^{4} - 10 {x}^{3} + 10 {x}^{2} - 5x + 1](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B5%7D++-++%7B%28x+-+1%29%7D%5E%7B5%7D++%3D+5+%7Bx%7D%5E%7B4%7D++-+10+%7Bx%7D%5E%7B3%7D++%2B+10+%7Bx%7D%5E%7B2%7D++-+5x+%2B+1)
Summing the R.H.S. and L.H.S. from n to 1 :
![{n}^{5} = 5 \sum {n}^{4} - 10\sum {n}^{ 3} + 10\sum {n}^{2} - 5\sum {n} + n {n}^{5} = 5 \sum {n}^{4} - 10\sum {n}^{ 3} + 10\sum {n}^{2} - 5\sum {n} + n](https://tex.z-dn.net/?f=+%7Bn%7D%5E%7B5%7D++%3D+5+%5Csum++%7Bn%7D%5E%7B4%7D++-+10%5Csum++%7Bn%7D%5E%7B+3%7D+%2B+10%5Csum++%7Bn%7D%5E%7B2%7D+-+5%5Csum++%7Bn%7D+%2B+n)
Putting the formula for the sums we know about :
![\sum {n}^{3} = {( \frac{n(n + 1)}{2} )}^{2} \sum {n}^{3} = {( \frac{n(n + 1)}{2} )}^{2}](https://tex.z-dn.net/?f=%5Csum++%7Bn%7D%5E%7B3%7D+%3D++%7B%28+%5Cfrac%7Bn%28n+%2B+1%29%7D%7B2%7D+%29%7D%5E%7B2%7D+)
![\sum {n}^{2} = \frac{n(n + 1)(2n + 1)}{6} \sum {n}^{2} = \frac{n(n + 1)(2n + 1)}{6}](https://tex.z-dn.net/?f=%5Csum++%7Bn%7D%5E%7B2%7D+%3D++%5Cfrac%7Bn%28n+%2B+1%29%282n+%2B+1%29%7D%7B6%7D+)
![\sum {n} = \frac{n(n + 1)}{2} \sum {n} = \frac{n(n + 1)}{2}](https://tex.z-dn.net/?f=%5Csum++%7Bn%7D+%3D++%5Cfrac%7Bn%28n+%2B+1%29%7D%7B2%7D+)
Putting these formula in above relation and simplifying :
![\sum {n}^{4} = \frac{n(n + 1)(2n + 1)(3 {n}^{2} + 3n - 1)}{30} \sum {n}^{4} = \frac{n(n + 1)(2n + 1)(3 {n}^{2} + 3n - 1)}{30}](https://tex.z-dn.net/?f=%5Csum++%7Bn%7D%5E%7B4%7D+%3D++%5Cfrac%7Bn%28n+%2B+1%29%282n+%2B+1%29%283+%7Bn%7D%5E%7B2%7D++%2B+3n+-+1%29%7D%7B30%7D+)
Using Binomial Expansion :
Summing the R.H.S. and L.H.S. from n to 1 :
Putting the formula for the sums we know about :
Putting these formula in above relation and simplifying :
Similar questions